Perencanaan Sistem Informasi untuk Mendukung Analisis Pemasaran menggunakan Metode EAP pada PT. Cherokendo Benua Wisata - Tegar Aryo Sulthon Musthofa; Gunawan Wang (Engineering, MAthematics and Computer Science (EMACS) Journal, 2019)
This case study conducted for information system planning by applying EAP methodology on PT. Cherokendo Benua Wisata. EAP is an approach to building a planned information system architecture. Case studies successfully identifed 12 business function and produces enterprise architecture. Architecture consists of data architecture, application architecture, and technology architecture. The Enterprise architecture can be use by company for guideline to develop information system.